Online Mindfulness May Target Psychological Distress and Mental Health during COVID-19 - Suzan R Farris BA; Licia Grazzi MD; Miya Holley BS; Anna Dorsett BS; Kelly Xing BS; Charles R Pierce MS; Paige M Estave BS; Nathaniel O'Connell PhD; Rebecca Erwin Wells MD, MPH, FAHS (SAGE Publishing, 2021)
Background The COVID-19 pandemic has dramatically affected mental health, creating an urgent need for convenient and safe interventions to improve well-being. Online mindfulness interventions show promise for improving depression, anxiety, and general well-being. Objective To assess: 1) the impact of online mindfulness on psychological distress, 2) altruistic efforts, and 3) the quantity, quality, and availability of online mindfulness resources during the COVID-19 pandemic. Methods 233 participants (203 U.S.; 20 international; 10 unknown) participated in this prospective, single-arm, non-randomized clinical trial of a single online mindfulness meditation session with pre- and post-surveys. Main Outcome Measures (a) Mindfulness session helpfulness, online platform effectiveness, and immediate pre- to post-session changes in momentary stress, anxiety, and COVID-19 concern; (b) qualitative themes representing how people are helping others during the pandemic; (c) absolute changes in quantity of mindfulness-oriented web content and free online mindfulness resource availability from May to August 2020. Results Most participants felt the online mindfulness session was helpful and the electronic platform effective for practicing mindfulness (89%, 95% CI: [82 to 93%]), with decreased momentary anxiety (76%; 95% CI: [69 to 83%]), stress (80%; [72 to 86%]), and COVID-19 concern (55%; [46 to 63%]), (p < 0.001 for each measure). Participants reported helping others in a variety of ways during the pandemic, including following public health guidelines, conducting acts of service and connection, and helping oneself in hopes of helping others. "Mindfulness + COVID" search results increased by 52% from May to August 2020. Most (73%) Academic Consortium for Integrative Medicine and Health member websites offer free online mindfulness resources. Conclusions Virtual mindfulness is an increasingly accessible intervention available world-wide that may reduce psychological distress during this isolating public health crisis. Kindness and altruism are being demonstrated during the pandemic. The consolidated online mindfulness resources provided may help guide clinicians and patients.